2007
DOI: 10.1002/app.27079
|View full text |Cite
|
Sign up to set email alerts
|

Properties and pervaporation separation of hydroxyl‐terminated polybutadiene‐based polyurethane/poly(methyl metharcylate) interpenetrating networks membranes

Abstract: Hydroxyl-terminated polybutadiene (HTPB), 4,4 0 -dicyclohexyl methane diiscyanate (H 12 MDI), and 1,4-butane diol are used to synthesize polyurethane (PU) solutions by two-stage process. Interpenetrating networks (IPNs) of HTPB-based PU and poly(methyl methacrylate) (PMMA) with HTPB/MMA (wt/wt % ratio) 5 2.0, 1.5, 1.0, 1.5, 0.8, and 0.6, which are designated as IPN1 to IPN5, respectively, are synthesized by sequential polymerization technique. Thermal properties, tensile strength, and contact angle of membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…This higher storage modulus can be attributed to an increase in the PMMA component in this synthetic IPN. It can be concluded that increasing PMMA content in the IPN results in an increase in the polymeric strength (7). This may be a reason for increasing the storage modulus of 65/35 IPN relative to the other two synthetic IPNs (i.e., 75/25 and 85/15 IPNs).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This higher storage modulus can be attributed to an increase in the PMMA component in this synthetic IPN. It can be concluded that increasing PMMA content in the IPN results in an increase in the polymeric strength (7). This may be a reason for increasing the storage modulus of 65/35 IPN relative to the other two synthetic IPNs (i.e., 75/25 and 85/15 IPNs).…”
Section: Discussionmentioning
confidence: 93%
“…polyol having at least two reactive hydrogen atoms. However, the applications of PU are limited due to its low mechanical strength and poor thermal stability (7).…”
Section: Introductionmentioning
confidence: 99%
“…It is a regular measure of the surface hydrophobicity that provides information on the hydrophobic or hydrophilic surface at the air-watersolid interface. 41 High contact angles between 70 and 90 indicate strongly hydrophobic surfaces such as those of fluorocarbon polymers, whereas low contact angles (0-30 ) indicate highly hydrophilic surfaces such as those of glass and mica. 42 The contact angles against water increased with the PVDF content in the blend films, and this was caused by the hydrophobicity of PVDF due to the CF 2 group of PVDF.…”
Section: Contact-angle Studymentioning
confidence: 99%
“…A group of polymers used as components of IPNs or semi-IPNs are polybutadienes with predominant 1,4-structure [8][9][10][11][12][13][14][15][16][17]. One of the most common investigations is preparation of IPNs [8][9][10][11]13] or semi-IPNs [12] with methacrylic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common investigations is preparation of IPNs [8][9][10][11]13] or semi-IPNs [12] with methacrylic polymers. In a typical procedure hydroxylterminated butadiene was reacted with isocyanate, and the resulting polymer was swollen with a methacrylate, dimethacrylate, or mixture of methacrylates of various functionality which was then polymerized to form IPN.…”
Section: Introductionmentioning
confidence: 99%